2017
DOI: 10.1016/j.foreco.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Generalized biomass and leaf area allometric equations for European tree species incorporating stand structure, tree age and climate

Abstract: Biomass and leaf area equations are often required to assess or model forest productivity, carbon stocks and other ecosystem services. These factors are influenced by climate, age and stand structural attributes including stand density and tree species diversity or species composition. However, such covariates are rarely included in biomass and leaf area equations. We reviewed the literature and built a database of biomass and leaf area equations for 24 European tree species and 3 introduced species. The final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
194
1
25

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(242 citation statements)
references
References 73 publications
4
194
1
25
Order By: Relevance
“…However, when height alone was used, the AB biomass prediction bias between pure and mixed stands (at approximately 19%, Table 3) was greater than using DBH alone (approximately 15%, Table 3). Biomass predictions that include height and wood density as covariates with DBH can be effective in offsetting site and species effects (Wirth et al 2004, Chave et al 2014, Forrester et al 2017b). This is related to H-DBH relationship being one of the main influences of biomass-DBH site variability and to species variations in wood density.…”
Section: Why Was the Biomass Allometry Of Pure Trees Different From Tmentioning
confidence: 99%
“…However, when height alone was used, the AB biomass prediction bias between pure and mixed stands (at approximately 19%, Table 3) was greater than using DBH alone (approximately 15%, Table 3). Biomass predictions that include height and wood density as covariates with DBH can be effective in offsetting site and species effects (Wirth et al 2004, Chave et al 2014, Forrester et al 2017b). This is related to H-DBH relationship being one of the main influences of biomass-DBH site variability and to species variations in wood density.…”
Section: Why Was the Biomass Allometry Of Pure Trees Different From Tmentioning
confidence: 99%
“…For branch and foliage, the negative coefficient of BA implies that for a given DBH and A, trees growing in stands with higher stocking will have lower crown biomass than trees growing in less stocked stands. (12) The only difference between this system (Equation (12)) and the system IV (Equation (10)) is associated with the branch biomass equation. In addition to DBH and HT, the branch biomass equation included BA in system VI, instead of including A in the system IV.…”
Section: Model Fittingmentioning
confidence: 99%
“…These models are widely used but limited to certain stand characteristics and geographical areas, particularly those from which the data originated. However, inclusion of additional stand variables in the models such as stand age, density and/or productivity may result in general models that provide more accurate predictions [10][11][12]. Moreover, Gonzalez-Benecke et al [10] concluded that stand characteristics used as covariates in general biomass functions resulted in significant improvements in model fitting and prediction ability for all tree components, especially when age and HT were unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Modelling by employing mixed models, as used by Forrester et al [74], Grote et al [75], and Pretzsch et al [76] has the advantage of being applicable at different geographical and differently structured sites. In this study, RCD had the strongest correlation with BMD (M 01 ).…”
Section: Correlation Of Stand Parameter and Allometric Biomass Modelsmentioning
confidence: 99%